(untitled) (مجلة التربوي, 2025)
This study delves into the various challenges and difficulties faced by English as a Second Language (ESL) tutors when teaching Korean students through one-on-one sessions online. This study purports to measure the difficulties encountered by English as Second Language (ESL) tutors by conducting in-depth interviews with ESL tutors who are experienced enough both in working with Korean students and in virtual online settings to explore issues such as communication difficulties, contradicting expectations from learning interactions and cultural differences which can affect methods that are commonly used in an ESL instruction or teaching. The findings of this study showed that the challenges faced by ESL tutors were from language and infrastructural barriers which caused the flow of their class to be affected. The difficulty that comes with understanding what a Korean student means causes ESL tutors to prepare visual aids and translators so that they may be understood. Constant infrastructural barriers such as poor internet service also caused disruption in the flow of the class for most ESL tutors which eventually resulted to some tutors canceling the class. On the other hand, other challenges reported were the online class format and students' engagement and participation. Most tutors reported that student participation eventually declines as the class progresses and students are able to communicate more comfortably and effectively. The research also highlighted the issue of the lack of formal training for ESL tutors. Tutors who were interviewed revealed that they had to rely heavily on their experienced co-workers for them to have an idea about ESL teaching. Recommendations of this study included developing a more comprehensive training for aspiring ESL tutors, beginner-friendly class materials, and teaching methods that can both increase student engagement and are culturally appropriate. These solutions and alternatives can contribute to a better way of teaching Korean students in the online learning environment, which can ultimately help them in absorbing and acquiring the English language.